Penelusuran Potensi Antioksidan Dalam Beragam Ekstrak Daun Tanaman Obat Di Indonesia - Mutiara Hati, Nadia; Triyandi, Ramadhan; Wardhana S, Muhammad Fitra; Andrifianie, Femmy; Iqbal, Muhammad (Medula, 2024)
Antioxidants are substances that are able to absorb or neutralize free molecules, preventing degenerative diseases such as heart disease and cancer by donating electrons to inhibit free radical chain reactions that damage the body. The use of natural medicines is increasingly becoming the main choice in Indonesian society. Even though various types of plants have been used for a long time, their use has not been optimal. In order to summarize and provide information regarding the potential of natural ingredients from various plant extracts which have antioxidant activity, a literature review was carried out. The method used was a database search via Google Scholar for the last 8 years (2015-2023), which produced 170 journals regarding plants with antioxidant activity. Of this number, 20 plants were selected based on the dark green leaves which have antioxidant activity by comparing the IC50 values ​​obtained. Plant extracts contain antioxidant compounds that can fight free radicals, offering a natural alternative to synthetic antioxidants.  Plants with high antioxidant activity often have characteristics such as phytochemical content such as flavonoids, polyphenols, carotenoids, and vitamin C, as well as bright colors such as purple, red, or orange which indicate the content of antioxidant pigments such as anthocyanins, lycopene, or beta-carotene. Apart from that, plants that have a bitter or astringent taste, such as green tea, red grapes, or blueberries, also tend to contain quite high levels of antioxidant compounds, coupled with their habit of growing in harsh or extreme environments and their traditional use in medicine or health supplements.